2011
DOI: 10.1039/c1dt10340g
|View full text |Cite
|
Sign up to set email alerts
|

Substituted pyridazines as ligands in homoleptic (fac and mer) and heteroleptic Ru(ii) complexes

Abstract: This article reports the preparation of a range of phenyl, pyridyl and pyrazinyl substituted pyridazines via the inverse electron demand [2 + 4] Diels-Alder reaction between 3,6-di(2-pyridyl)-1,2,4,5-tetrazines (bptz) and 3,6-di(2-pyrazinyl)-1,2,4,5-tetrazines (bpztz) and suitable dienophiles including acenaphthalene. The resulting polyaromatic compounds vary systematically in the number of aromatic substituents and the number and position of N-heteroatoms. For four of these compounds, the effect of the molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Previously, iEDDA reactions have been predominantly used for the preparation of pyridazines, which were applied as nitrogen donor ligands 3 . In 2008, however, two groups independently discovered that the fast and selective iEDDA reaction of strained olefins and tetrazines can be used in the sense of ‘click chemistry’ fulfilling most of Sharpless’ criteria 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, iEDDA reactions have been predominantly used for the preparation of pyridazines, which were applied as nitrogen donor ligands 3 . In 2008, however, two groups independently discovered that the fast and selective iEDDA reaction of strained olefins and tetrazines can be used in the sense of ‘click chemistry’ fulfilling most of Sharpless’ criteria 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…A synthetic protocol which can be extended to multiple systems is very attractive and new aromatic ligands generated by Diels-Alder cycloaddition have come to the fore in Ru(II) chemistry. [7][8][9][10] One development in copper chemistry has been the inclusion of stabilizing phosphine ligands, offering a significant improvement on the photophysical properties. McMillin and co-workers have demonstrated that bulky bidentate phosphines (such as POP = bis [2-(biphenylphosphino)phenyl]ether) inhibit the formation of quenching exciplexes, providing unusually long emission lifetimes and rather good quantum yields, typically in the green spectral window.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is well-known that coordination of this type of ligands often results in a mixture of facial and meridional stereoisomers in a statistical 1:3 ratio (Figure a) . However, these isomers can have different photophysical, electrochemical, and magnetic properties, with appealing applications in OLEDS, ,, catalysis , or supramolecular chemistry. Considering that isolation of these isomers can be extremely challenging, especially in the case of labile complexes, attaining control over the fac / mer stereoisomerism is thus of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the development of photoactive iron complexes is currently a hot topic within the scientific community. Despite the challenging photophysics of typical polyimine Fe complexes, charge transfer-excited states with lifetimes ranging from hundred of picoseconds , up to few nanoseconds have been achieved. These impressive results are the consequence of judicious ligand designs, with N-heterocyclic carbenes (NHC), , cyclometallating units, or amides playing a pivotal role in the creation of sufficiently high ligand fields.…”
Section: Introductionmentioning
confidence: 99%